Making democracy work for pro-poor development (Commonwealth Secretariat LondonGB, 2003)
Attempts to examine patterns of development and democracy worldwide. Pays special attention to the experiences of development and democracy throughout the Commonwealth, especially among the more vulnerable communities including small states. Outlines a new approach to development and democracy and suggests that the crisis of global poverty and weaknesses of democratisation processes in many countries can be addressed by using democratically-oriented policies to tackle poverty.
Keywords: DEVELOPMENT STRATEGY